(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The widespread occurrence of various pathologies of the cardiovascular system (CVS) among the human population requires the creation of non-invasive instrumental methods and diagnostic tools aimed at early detection and prevention of pathological conditions of the myocardium. Stress testing is most often used as a non-invasive and reproducible method for diagnosing the condition and prognosis of treatment of human CVD. The stress testing system includes simulators on which the patient performs physical activities of a certain capacity (bicycle ergometer, treadmill), sensors for recording human biological signals (for example, an electrocardiogram of blood pressure) and computing devices for processing the data obtained with the necessary software. Cardiopulmonary stress testing (CPNT) refers to stress stress testing with additional measurement of gas exchange parameters at rest, during exercise and during recovery.